Returns to Postgraduate Education in Indonesia: Province-Level Evidence and Policy Implications - Ahmad Arib Al Farisy; Devi Sartika; Lena Elfianty; Jusuf Wahyudi; Chisillia Mayangsari; Sarah Ulfah Al Amany (Universitas Dharma Wacana, 2024)
This study investigates the relationship between postgraduate education (Master's and Doctoral degrees, designated S2/S3 in Indonesia's educational system) and provincial-level economic outcomes using comprehensive 2022 data from Indonesia's Central Statistics Agency (BPS). Drawing on human capital theory (Becker, 1964; Mincer, 1974) and signaling theory (Spence, 1973), we examine how the concentration of advanced degree holders correlates with key development indicators across Indonesia's 34 provinces. Our cross-sectional analysis employs Pearson correlations with heteroscedasticity-robust standard errors and multiple regression specifications controlling for urbanization, industrial composition, and geographic factors. Results reveal significant positive correlations between postgraduate education rates and economic prosperity. Provinces with higher concentrations of S2/S3 degree holders demonstrate substantially higher GDP per capita (r = 0.52, p < 0.01), Human Development Index scores (r = 0.71, p < 0.001), and lower poverty rates (r = -0.48, p < 0.01). DI Yogyakarta leads with a postgraduate rate of 1.11%, while Nusa Tenggara Timur lags at 0.21%, highlighting significant regional disparities. These findings are robust to the exclusion of outliers (DKI Jakarta, Papua) and persist across alternative model specifications. While cross-sectional data precludes causal inference, the strength and consistency of associations provide empirical support for expanding government scholarship programs such as LPDP (Lembaga Pengelola Dana Pendidikan). We recommend targeted scholarship investments in underrepresented provinces and fields with high economic multiplier effects to address regional disparities and maximize returns from educational investment